(untitled) (Herald of Journalism, 2026)
This article explores contemporary theories of digital communication and new methodological approaches, focusing on the context of Central Asian countries. The main objective is to identify the key theoretical directions of digital communication and to evaluate the methodological instruments employed in their study. In particular, in Central Asia, Telegram, Instagram, and YouTube platforms have replaced traditional media and become alternative communication channels. In the course of this study, using the example of «Vlast.kz», «Tengrinews.kz» in Kazakhstan, «Kloop.kg» in Kyrgyzstan and «Kun.uz» In Uzbekistan, new methodological approaches to active digital communications (infographics, data journalism, storytelling) were taken into account and a comparative analysis was conducted. Special emphasis is placed on the spread of the internet and social networks, the rise of multimedia communication systems, algorithmic governance, and participatory culture. In addition, the article addresses emerging challenges such as disinformation, post-truth dynamics, and the impact of algorithmic culture on audience perception. The research methodology combines comparative analysis with both qualitative and quantitative methods, which made it possible to trace the evolution of digital communication theories and highlight their divergence from traditional mass communication paradigms. Findings indicate that interactivity, openness, personalization, and hypermedia are among the defining features of digital communication that reshape social relations in modern society. The scientific contribution of this research lies in rethinking digital communication theories through a multidisciplinary lens, integrating network analysis, digital ethnography, and computational approaches. The practical relevance is found in applying these results to media practice, journalism, and educational contexts, providing tools for more effective communication in the digital environment.